Synthesis and characterization of silver nanowires via polyol process / Nurul Azri Khalisah Aznan - Nurul Azri Khalisah , Aznan (2016)
Silver nanowires (AgNWs) were successfully synthesized via polyol process mediated with different mediated and control agents. Morphological studies from Transmission Electron Microscopy (TEM) and Field Emission Scanning Electron Microscopy (FESEM) proved the formation of AgNWs with the diameter sizes in the range between 60 – 100 nm. X-ray Diffraction (XRD) patterns of as-synthesized samples showed the peaks that assigned to the face-centered cubic (FCC) silver (Ag) crystals which according to standard PDF card 04-0783. The peaks at angle 2θ around 38°, 44°, 64° and 75° are corresponding to (111), (200) and (311) crystal planes of the FCC Ag, respectively. Optical studies from UV-vis spectroscopy showed that the spectra have main peaks at wavelength around 410 nm which attributed to the transverse plasmon mode of AgNWs. The spectra also showed another shoulder peaks at wavelength around 350 nm which regarded to the plasmon resonance of long AgNWs.